ORGANIZATIONAL PREREQUISITES AND ANALYTICAL SIGNIFICANCE FOR ESTABLISHMENT OF THE 112 EMERGENCY CALL E-SYSTEM IN THE REPUBLIC OF SERBIA - Racić, Ilija; Anđelković, Maja (ACADEMIC REVIEW, 2025)
The goal of the research, the results of which are presented in this paper, was to identify, scientifically describe, classify and partially explain the organizational changes that are necessary for the establishment of the 112 emergency call system, and to point out the analytical importance of reporting and information in emergencies in the Republic of Serbia. Given the fact that the 112 emergency call system has not been seriously analyzed in domestic scientific and professional literature, the paper presents the results of the research, which was aimed at finding an answer to the question: "Can the functioning of the police organization, fire-rescue organizations, and emergency medical services in the Republic of Serbia (and in what way) be improved by its organizational adjustment based on the consistent application of the emergency call system 112". The results of such directed theoretical-empirical research presented in this paper confirmed the point of view according to which appropriate adjustment of functiona, structural element, as well as timely and relevant analytical reporting and information, create a necessary prerequisite for effective and efficient establishment and application of the emergency call system in the Republic of Serbia. The scientific justification of the research derives from its expected results, which can: 1) contribute to the deepening and expansion of scientifically verified knowledge in the field of criminal-police, security, and organizational scientific disciplines, 2) indicate the directions, areas, and topics of future scientific researches and 3) enrich the methodological practice of scientific research of the organization and proactive functioning of the police, fire-rescue units and emergency medical services in modern conditions.